Impactos da pandemia de covid-19 nos eventos culturais brasileiros: adaptação e uso de lives como estratégias de marketing digita - Gonçalves, Isabelle Vitória de Castro (Brasil, 2024)
The health crisis caused by COVID-19 has had a profound impact on Brazilian cultural events, restricting public presence and imposing social distancing measures. The aim is to answer how the COVID 19 pandemic crisis affected cultural events and how lives on YouTube influenced consumers' experience and connection with these events? Digital marketing strategies have become essential for maintaining audience engagement, promoting events and offering innovative solutions for artists and organizers. This study had the general objective of analyzing how lives on YouTube influenced consumers' experience and connection with cultural events during the COVID-19 pandemic. The research used the inductive method, and the types of applied, quali-quanti, exploratory, documentary bibliographic and field research with case study. The qualitative and exploratory approach allowed us to obtain valuable insights into the phenomenon of cultural lives, highlighting both its role as a digital marketing strategy and its limitations and opportunities for improvement. The main result was that lives provide flexibility and accessibility to cultural events in periods of social isolation.